Regulation of Gelatinase Activity in Mice with Targeted Inactivation of Components of the Plasminogen/Plasmin System - Lijnen, H. R.; Silence, J.; Lemmens, G.; Frederix, L.; Collen, D. (Thrombosis and Haemostasis, 1998)
To investigate a potential physiological role of the plasminogen/ plasmin system in activation of the matrix metalloproteinase (MMP) system, the distribution of latent and active MMP-2 (gelatinase A) or MMP-9 (gelatinase B) was monitored in aorta extracts and in serum-free conditioned cell culture medium obtained from wild-type (WT) mice and from mice with deficiency of tissue-type plasminogen activator (t-PA–/–), urokinase-type plasminogen activator (u-PA–/–), plasminogen activator inhibitor-1 (PAI-1–/–) or plasminogen (Plg–/–).In aorta extracts, the contribution of active MMP-2 to the total MMP-2 level ranged between 7 and 16% for the different genotypes, whereas active MMP-9 was not detected.The contribution of active 58 kDa MMP-2 to the total MMP-2 level (active plus latent) ranged between 14 and 29% (mean of 3 experiments) for fibroblasts of the different genotypes, and between 18 and 32% for smooth muscle cells, and was relatively constant in time (7-72 h). The contribution of active 83 kDa MMP-9 to the total MMP-9 level ranged between 15 and 29% for fibroblasts of the different genotypes and was relatively constant in time (24-72 h); corresponding values were 17 to 57% for smooth muscle cells, with the exception of Plg–/– smooth muscle cells which had undetectable levels of active MMP-9. Addition of plasmin(ogen) to the cell culture medium of fibroblasts did not significantly affect the distribution of active and latent MMP-2, but resulted in an approximately two-fold enhancement of the contribution of active MMP-9. In macrophages of Plg–/– mice, active MMP-9 was detected only when the cells were cultured in the presence of plasminogen.These data indicate that activation of proMMP-2 occurs independently of the physiological plasminogen activators and of plasmin(ogen) in all the cell types evaluated. Activation of proMMP-9 was enhanced in the presence of plasmin(ogen), but active MMP-9 was also detected in fibroblasts of Plg–/– mice, indicating that in vivo activation may occur via plasmin(ogen)-independent mechanisms.